The Routledge handbook of postcolonial social work - Kleibl, Tanja (Routledge; London and New York:., 2020)
"The Routledge Handbook of Postcolonial Social Work reflects on and dissects the challenging issues confronting social work practice and education globally in the post-colonial era. By analyzing how countries in the so called developing and developed world have navigated some of the inherited systems from the colonial era, it shows how they have used them to provide relevant social work methods which are also responsive to the needs of a post-colonial setting. This is an analytical and reflexive handbook that brings together different scholars from various parts of the world - both North and South - so as to distill ideas from scholars relating to ways that can advance social work of the South and critique social work of the North in so far as it is used as a template for social work approaches in post-colonial settings. It determines whether and how approaches, knowledge-bases and methods of social work have been indigenized and localized in the Global South in the post-colonial era. This handbook provides the reader with multiple new theoretical approaches and empirical experiences and creates a space of action for the most marginalized communities worldwide. It will be of interest to all social work students, researchers and practitioners"--
Includes bibliographical references and index.
Keywords: Social service -- Practice -- Developing countries; Social service -- Practice -- Cross-cultural studies; Postcolonialism -- Developing countries